Magnetocaloric and Elastocaloric Effects in All‐d‐Metal Ni37Co9Fe4Mn35Ti15 Magnetic Shape Memory Alloy. Issue 23 (21st October 2019) - Liu, Shilong; Xuan, Haicheng; Cao, Ting; Wang, Libang; Xie, Zhigao; Liang, Xiaohong; Li, Hui; Feng, Lin; Chen, Fenghua; Han, Peide
Abstract : The magnetocaloric effect and the elastocaloric effect in a polycrystalline all‐d‐metal Ni37 Co9 Fe4 Mn35 Ti15 magnetic shape memory alloy are investigated. The alloy undergoes a transition from ferromagnetic austenite to weak‐magnetic martensite near room temperature. It exhibits a maximum magnetic entropy change of 8.4 J Kg −1  K −1 under the magnetic field of 3 T. Moreover, a maximum temperature change of 6.3 K associated martensite transition is obtained at room temperature by loading the uniaxial stress of 400 MPa. These results suggest that the alloy is the promising candidate for new solid‐state refrigeration materials. Abstract : The Ni37 Co9 Fe4 Mn35 Ti15 undergoes a transition from ferromagnetic austenite to weak‐magnetic martensite with the application of the magnetic field and uniaxial stress. It is found that the alloy exhibits a magnetic entropy change of 8.4 J Kg −1  K −1 under the magnetic field of 3 T and a maximum temperature change of 6.3 K under 400 Mpa during the transition.